(untitled) (Al-Mansour Journal, 2026)
Because of the digit development height since (2019) and the result market demand for data security investigate, it grows speedy and more than adequately with an obligation to form a huge scope of electronic mark examine. These range from classical embedded designs, through revocable and certificate-linked signatures to aggregate signatures, multi-party signatures for the wide system setting and finally privacy preserving blind signatures. It also includes post-quantum methods and proposals for blockchain environments and embedded systems, traffic, and vehicle areas. The selected and compared research works are presented in this manuscript for the years 2023 to 2025 by jointly collecting them on different features including key generation or setup cost, signature size, signature time, cycles of computation, verification time and communication cost as well as system-level load reduction. The equivalency illuminates that no one approach performs best on all measures. For aggregate and hierarchical schemes, more signature scalability is yielded at the cost of larger signatures compared to classical embedded signature schemes. We further remark that post-quantum designs are becoming more suitable and suitability-oriented through providing tech-practical trade-outs for blockchain, IoT, to a lesser extent also hardware delegates. (EdDSA) and (ECC) will still be good preferred choices for applications which require high efficiency with reasonable to strong security, while (RSA) will still stay a suitable candidate & preferred choice for legacy systems or situations were compatibility and compliance are critical driver as always.